2011
DOI: 10.1093/bja/aeq333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose preoperative methylprednisolone on pain and recovery after total knee arthroplasty: a randomized, placebo-controlled trial

Abstract: MP 125 mg before surgery improves analgesia and immediate recovery after TKA, even when combined with a multimodal analgesic regime. These findings call for further studies on safety aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
225
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(254 citation statements)
references
References 35 publications
21
225
0
2
Order By: Relevance
“…Our findings agree with those of previous small series [15,36,38,40] and reviews of numerous perioperative settings [19,21,22,46] that found no association between corticosteroid use and increased risk for postoperative wound infection. Furthermore, studies using higher corticosteroid doses than that used in our study showed no increase in postoperative wound infection after major orthopaedic surgeries [1,5,19,25,46].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings agree with those of previous small series [15,36,38,40] and reviews of numerous perioperative settings [19,21,22,46] that found no association between corticosteroid use and increased risk for postoperative wound infection. Furthermore, studies using higher corticosteroid doses than that used in our study showed no increase in postoperative wound infection after major orthopaedic surgeries [1,5,19,25,46].…”
Section: Discussionsupporting
confidence: 93%
“…Patients who received dexamethasone experienced lower pain and consumed less opioid during the 6-to 24-hour postoperative period compared with patients who received ramosetron alone. These findings agree with those of two recent studies that showed that 125 mg of methylprednisolone reduced resting pain for 2 to 48 hours and reduced opioid consumption for the first 24 hours in 24 patients who had unilateral TKA [38], and that 300 mg hydrocortisone reduced postoperative pain and epidural medication for the first 24 hours in 17 patients who had bilateral TKAs concurrently treated with a multimodal analgesic regimen [24] (Table 4). Our results and those of previous studies [24,38] suggest that incorporation of corticosteroids in a multimodal analgesic regimen provides synergistic analgesia and opioid-sparing effects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The efficacy of glucocorticoids as part of multimodal postoperative pain treatment in different surgical procedures has recently been reviewed [20] demonstrating reductions in both pain scores and morphine consumption. Likewise, Lunn et al [21] showed that IV methylprednisolone 125 mg after total knee arthroplasty improved analgesia and promoted recovery. Neither of the studies reported on serious complications, especially wound infection, from the use of a single dose of glucocorticoids, but calls for further largescale studies on safety issues.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of OI was not significantly reduced with midodrine (risk ratio, 0.63; 95% confidence interval, 0.36 to 1.10; P = 0.10), further studies with higher dosing and earlier premobilization administration may be warranted. Furthermore, targeting the postoperative inflammatory response with high-dose systemic glucocorticoids-which has shown to have some effect on reducing pain, opioid requirements, inflammatory response, and early fatigue after THA, TKA, 18,19 and endovascular aortic aneurism repair-20 could potentially reduce the incidence of OH and OI during early postoperative mobilization. Indeed, this is currently being studied in THA patients (www.…”
Section: Interventions To Reduce Postoperative Oimentioning
confidence: 99%